The efficacy of Jujube syrup on the prevention of drug‐induced hepatotoxicity in pulmonary tuberculosis patients: A pilot randomized double‐blind placebo‐controlled clinical trial - Seyedeh Zahra Maddahi; Assie Jokar; Mohammad Kamalinejad; Nasser Behnampur (Pharmacology Research & Perspectives, 2022)
Abstract Liver injury is the most common complication of anti‐tuberculosis drugs that can cause significant problems. The study aimed to determine the effectiveness of Jujube syrup on the prevention of antituberculosis drug‐induced hepatotoxicity (DIH). This pilot randomized double‐blind study was conducted based on a placebo‐controlled design in patients with tuberculosis (TB). The patients were divided into two groups based on the block random allocation method and received 10 cc of jujube or placebo syrup per day. The liver enzyme levels were assessed as primary outcomes, and the severity of cough, anorexia, and nausea along with the quality of life (QOL) was assessed as secondary outcomes. Finally, eight and nine patients in the jujube and placebo groups completed the study, respectively. In the second week of the study, 27.3% of the patients in the placebo group developed hepatotoxicity. Moreover, there was no liver toxicity in the jujube group. This difference between the two groups was statistically significant (p = .037). Furthermore, the severity of cough in patients in the jujube group decreased significantly during weeks 2 and 4. The QOL significantly improved in the jujube group, compared to the placebo group. This study suggested that Jujube syrup could prevent anti‐TB DIH. It can also improve the severity of cough and the QOL in pulmonary TB patients.